DETERMINATION OF TOTAL PHENOL, FLAVONOID CONTENT, AND PHYTOCHEMICAL SCREENING OF ETHYL ACETATE EXTRACT OF RAMBUTAN LEAVES (NEPHELIUM LAPPACEUM L.) - Hidayati, Amelia; Norhayati, Norhayati; Sayakti, Putri Indah (Acta Pharmaceutica Indonesia, 2025)
Medicinal plants are included in the abundant biodiversity heritage in Indonesia, including the South Kalimantan region, which still uses many plants in medicine. Rambutan (Nephelium lappaceum L.) is a plant known to contain phenolic compounds and flavonoids that have potential as therapeutic agents. This study was conducted to analyze the total phenol and flavonoid levels by UV-Vis spectrophotometric method and phytochemical screening. Extraction was carried out on rambutan leaves using the soklet method with ethyl acetate solvent. The results of phytochemical screening showed that the ethyl acetate extract of rambutan leaves contained phenol compounds, flavonoids, alkaloids, tannins, saponins, steroids, and triterpenoids. Determination of total phenol content was measured using Folin-Ciocalteu reagent with standard gallic acid comparison solution, while determination of total flavonoid content was measured using AlCl3 reagent with standard quercetin comparison solution. The total phenol content obtained from the ethyl acetate extract of rambutan leaves was 437.69 mgGAE/gram (43.76%), while the total flavonoid content was 81.490 mgQE/gram (8.14%). Based on the results of the study, it can be concluded that the ethyl acetate extract of rambutan leaves contains significant total flavonoid and phenol levels and contains secondary metabolite compounds so that it has the potential to be used in medicine.